Mobility engineering : proceedings of CAETS 2015 Convocation on Pathways to Sustainability - Tandon, Mahesh Chandra; Ghosh, P., 1947- (Springer, 2017)
The book contains the proceedings of CAETS 2015 Convocation on?Pathways to Sustainability: Energy, Mobility and Healthcare Engineering? that was held on October 13-14, 2015 in New Delhi. This 3 volume proceedings provide an international forum for discussion and communication of engineering and technological issues of common concern. This volume talks about?Mobility? and includes 14 chapters on diverse topics like creating sustainable transportation systems, mobility of the future, unique engineering features like Delhi metro, digitally re-imagining mobility, trends and future strategies of transportation electrification, etc. The contents of this book will be useful to researchers, professionals, and policy makers alike.